Life and death in Freud and Heidegger - Carel, Havi (Contemporary psychoanalytic studies, 2006)
Life and Death in Freud and Heidegger argues that mortality is a fundamental structuring element in human life. The ordinary view of life and death regards them as dichotomous and separate. This book explains why this view is unsatisfactory and presents a new model of the relationship between life and death that sees them as interlinked. Using Heidegger's concept of being towards death and Freud's notion of the death drive, it demonstrates the extensive influence death has on everyday life and gives an account of its structural and existential significance. By bringing the two perspectives tog.